ANALISIS PROSES REKRUTMEN KARYAWAN DI HOTEL SHERATON BANDUNG - Muhamad Mukti Ali; Dicky Maryono (Economicus : Jurnal Ekonomi dan Manajemen, 2024)
In recruiting employees, Sheraton Hotel has specific criteria that candidates must meet. These criteria include the requirement to undergo two assessments and several other recruitment sessions to ensure that the hired workforce aligns with the values of hotel service. The high standards and multiple selection stages can result in a shortage of applicants who meet all the criteria, thereby prolonging the recruitment process. The expected benefit is effective recruitment. In an effective recruitment process, the more applicants there are, the more selective the company can be. This study aims to analyze the recruitment process carried out by the human resource department at Sheraton Hotel Bandung, with the goal of understanding and improving this recruitment process are: a). To determine the recruitment system used by hotel sheraton bandung. b). To understand the employee recruitment process applied at hotel sheraton bandung. Using qualitative methods and data collection through interviews, observations, and document reviews. This results in qualitative data in the form of written and spoken words from the interviewees. The results of the research indicate that the recruitment process still does not yield satisfactory outputs, such as errors that may be made by applicants or hr. Factors include applicants' lack of diligence in applying. The solution to this case is to identify the problems faced when applying through web-based job vacancy platforms.